The Role of Empathy and Relationship Quality in Building Customer Loyalty in Community Pharmacies: Evidence from Jordan - Almomani, Hamzeh; Alabbadi, Ibrahim; Alshuraideh, Muhammad Turki (Jordan Journal of Pharmaceutical Sciences, 2024)
Aim: This study explores how pharmacist empathy influences customer loyalty through the mediating role of relationship quality in community pharmacies. Methodology: A cross-sectional study utilizing a web-based questionnaire and convenience sampling was conducted in Jordan. Data were analyzed using Structural Equation Modeling (SEM). Results: A total of 536 responses were gathered and analyzed from all Jordanian regions. The gender distribution was balanced, with 261 males (48.7%) and 275 females (51.3%). The age distribution was concentrated in the 35-44 age group (29.3%), followed by 25-34 (25.6%). The majority had a high level of education, with 323 (60.3%) holding a Bachelor's degree or higher academic qualification (19.0%). Most participants visited pharmacies at least once every six months (50.6%), primarily using independent community pharmacies (52.1%). The study findings highlight a significant positive impact of pharmacist empathy on the three key dimensions of pharmacist-patient relationship quality (trust, satisfaction, and commitment). Furthermore, a significant positive relationship was found between the relationship quality dimensions and both customer loyalty dimensions (attitudinal and behavioral loyalty). Conclusion: The study findings highlight the central role of pharmacist empathy in establishing a strong and enduring pharmacist-patient relationship quality, which in turn, enhance consumers loyalty, which is essential for thriving and surviving in today's competitive market.